Dampak wisata halal terhadap kepuasan berkunjung wisatawan ke wisata taman syariah pamah simelir kabupaten langkat Sumatera utara - Adit, Masditou (Tourism, Hospitality And Culture Insights Journal, 2024)
Halal tourism aims to increase tourist satisfaction in the tourism industry in the Sharia Tourism Park. The main problem in this study is because there are still weaknesses in tourism in terms of facilities, services and cleanliness in tourist attractions. This study aims to determine how the impact of halal tourism on tourist satisfaction and also how the satisfaction of tourists visiting the Sharia Tourism Park. In this study, the author uses a field research approach (field research) data is analyzed with validity tests, reliability tests and simple regression tests (t-tests) using the SPSS 20.0 application. the results of the study show that halal tourism has a significant impact on the satisfaction of tourists visiting the Sharia Tourism Park. The percentage level of impact can be seen from the R square is 58.4%, while the remaining 41.6% is influenced by other factors.